Differential disease tolerance mediates sex-biased illness severity in sepsis - Breenna Dobson; Kathryn Strayer; Ayesha Wijesinghe; Jared Schlechte; Oscar Tejada; Alexandria Bartlett; Matthew Stephens; Diana Changirwa; Nicole A. Cho; Ian-ling Yu; Nargis Khan; Braedon McDonald (Proceedings of the National Academy of Sciences, 2026)
Sepsis in humans, as well as mouse models of infection, demonstrates sex-biased outcomes in which males tend to have a higher incidence, higher severity, and higher mortality compared to females. Despite this important sex-bias in sepsis outcomes, little is known about its mechanistic drivers nor therapeutic implications. Much of the foundational data on sepsis pathogenesis is derived from animal studies that included only male subjects, potentially contributing to the notable paucity of successful mouse-to-human translation of sepsis therapeutics. In this study, we demonstrate that male-biased illness severity and organ dysfunction in mouse models of bacterial sepsis are mediated by impaired disease tolerance in males, involving impaired tolerogenic shifts in mitochondrial oxidative metabolism compared to females. Microbiological and immunological analyses of sepsis between males and females revealed that sex-biased disease tolerance was independent of infection resistance mechanisms, as well as canonical immune/inflammatory dysregulation. Therapeutic potentiation of mitochondrial tolerance with doxycycline neutralized sexual dimorphism of illness severity and organ dysfunction through a male-predominant treatment effect. These data reveal that biological sex is a fundamental determinant of illness severity and treatment responsiveness in sepsis through modulation of disease tolerance, which may be harnessed therapeutically to address sex-biased outcomes in sepsis.